THE DEVELOPMENT OF TEACHING MATERIALS FOR STUDENT WORKSHEETS IN LEARNING BUDDHIST RELIGIOUS EDUCATION FOR GRADE IV ELEMENTARY SCHOOLS - Purnama, Ita; Sukodoyo, Sukodoyo; Waluyo, Waluyo (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2022)
The purpose of this study is to describe the process of developing LKPD in the learning of Buddhist and Moral Education in Class IV Elementary School. The method used in this study is a research and development with an Analyze, Design, Develop, Implement, and Evaluate (ADDIE) approach. The data collection techniques used include observation, interviews, questionnaires, and documentation. The data credibility is assessed by transferability, dependability, confirmability, and logical validity. The data analysis techniques used for qualitative data are data collection, data reduction, presentation, decision making, and verification. The quantitative data were analyzed by a descriptive percentage theory. Based on the assessments of the three material experts, LKPD obtained a percentage of 93,75% in the good and decent categories. The average percentage gain from the two media experts was 77,5% with good and decent categories. The average percentage of prospective users, namely fourth grade students at SD Negeri Wates 01 was 91,25% in the good category, while the percentage of grade IV students at SD Negeri 01 Kenteng is 88,77% which indicates that it was in the good category. The percentage gain from practitioners who have used LKPD PAB is 91,25 % with good and decent categories. Based on the result of the validation and implementation tests from the experts, and pracititioners, it is shown that the PAB LKPD was feasible to be used as a teaching material.